Anthropometric evaluation of preschool children in the urban area of Cuenca, Ecuador - Díaz-Granda, Ruth; Huiracocha, Lourdes (Maskana, 2015)
A cross-sectional study involving 577 preschool children attending regular well-baby check-ups was performed. Children with pathological deviations were excluded. Weight, height and BMI were monitored, according to age subgroups and gender. Absolute and relative frequencies were obtained for the qualitative variables; the average and the SD for quantitative variables. Comparability of groups was determined by sex (χ2, p> 0.05) and age (Mann-Whitney, p> 0.05). Correlations were defined and plotted between weight/age, height/ age and BMI/age. The average anthropometry for the group was: weight 12,006 ± 2.636 kg; height 10.0 ± 86.3 cm; BMI 16.1 kg m-2 ± 1.7; men had higher averages. The nutritional status of the group was normal according to the ratio weight/age at 90.8%, height/age at 75.6%, BMI/age at 77.5%. They presented low height/age and 24.3% overweight/ obesity 4.7%. Males had a higher frequency of severely underweight, underweight, severely stunted, stunting, overweight risk and overweight. The correlation weight/age, height/age and weight/height in both sexes was >0.8; the correlation BMI/age was <-0.3. The survey demonstrated that all types of malnutrition were present, and the deficit height/age seems the most important nutritional bottle neck. Correlation weight/age, height/age and weight/height were positive and high. Improving the living conditions of Latin American countries showed no improvement in the nutritional status of the children surveyed.